Probing the surface of a sweet protein: NMR study of MNEI with a paramagnetic probe - Niccolai, Neri (Cold Spring Harbor Laboratory Press, 2001)
The design of safe sweeteners is very important for people who are affected by diabetes, hyperlipemia, and caries and other diseases that are linked to the consumption of sugars. Sweet proteins, which are found in several tropical plants, are many times sweeter than sucrose on a molar basis. A good understanding of their structure–function relationship can complement traditional SAR studies on small molecular weight sweeteners and thus help in the design of safe sweeteners. However, there is virtually no sequence homology and very little structural similarity among known sweet proteins. Studies on mutants of monellin, the best characterized of sweet proteins, proved not decisive in the localization of the main interaction points of monellin with its receptor. Accordingly, we resorted to an unbiased approach to restrict the search of likely areas of interaction on the surface of a typical sweet protein. It has been recently shown that an accurate survey of the surface of proteins by appropriate paramagnetic probes may locate interaction points on protein surface. Here we report the survey of the surface of MNEI, a single chain monellin, by means of a paramagnetic probe, and a direct assessment of bound water based on an application of ePHOGSY, an NMR experiment that is ideally suited to detect interactions of small ligands to a protein. Detailed surface mapping reveals the presence, on the surface of MNEI, of interaction points that include residues previously predicted by ELISA tests and by mutagenesis.